PENGARUH CITRA MEREK TERHADAP KEPUTUSAN PEMBELIAN DENGAN WORD OF MOUTH SEBAGAI VARIABEL INTERVENING (STUDI KASUS ONLINE SHOPPING SHOPEE PADA MAHASISWA RUSUNAWA II UNIVERSITAS ISLAM MALANG) - Dini Febriana Riyanto; N. Rachma; M. Hufron (UNIVERSITAS ISLAM MALANG, 2019)
ABSTRACTThis study aims to determine the effect of brand image on purchasing decisions through word of mouth as an intervening variable in shopee online shop users in Rusunawa II Malang Islamic University students. The variables used in this study are brand image variables, purchasing decisions and word of mouth as intervening variables. Data collected through the questionnaire method with the number of samples used as respondents as many as 65 respondents. The result of this research concludes that there is an influence between the variable brand image directly influences the purchase decision, brand image has a direct effect on word of mouth, word of mouth has a direct effect on purchasing decisions and brand image has an indirect effect on purchasing decisions through word of mouth as a variable intervening.Keywords: Brand Image, Purchase Decision, Word Of Mouth